Predicting the critical drawdown pressure of sanding onset for perforated wells in ultra‐deep reservoirs with high temperature and high pressure. Issue 9 (25th May 2021) - Lu, Yu; Xue, Chengwen; Liu, Tao; Chi, Ming; Yu, Jie; Gao, Han; Xu, Xiaohui; Li, Haitao; Zhuo, Yiran
Abstract: Perforated wells in ultra‐deep sandstone reservoirs are characterized by high reservoir temperature, high formation pressure, and high production, and sand production will cause severe safety hazards to these wells. Based on Drucker‐Prager (DP) rock failure criterion, a practical analytical model for predicting critical drawdown pressure (CDP) of sanding onset for perforated wells is established by comprehensively considering the influence of drag stress, formation water production, reservoir pressure depletion, temperature difference in the perforated wellbore. The proposed model is verified by field sanding onset monitoring data. The calculation results show that CDP changes with well inclination, and it decreases with the increase in wellbore temperature difference, reservoir pressure depletion, and water saturation. However, the CDP increases with the number of perforations and the ratio of diameter to length. The optimization of perforation parameters has an important influence on sand control. This study can effectively guide the prediction of CDP and provides basis for efficient and safe development of similar ultra‐deep and high yield sandstone reservoirs. Abstract : A practical analytical model is established for prediction of critical drawdown pressure of sanding onset for perforated wells in deep wells. The proposed model is verified by field sanding onset monitoring data. This study can effectively guide the prediction of critical drawdown pressure and provides basis for efficient and safe development of similar ultra‐deep and high yield sandstone reservoirs.